2013
DOI: 10.3834/uij.1944-5784.2013.04.04
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Clinical Study to Compare the Efficacy and Safety of Naftopidil Versus Tamsulosin in Symptomatic Benign Prostatic Hyperplasia

Abstract: Aim:To compare the clinical efficacy and tolerability of naftopidil versus tamsulosin in patients with LUTS due to BPH. Tamsulosin acts via α1A-receptor and naftopidil acts via α1D-receptor blocker. The latter is believed to be more efficacious with fewer side effects. settings and Design: A prospective, randomized, non-placebo clinical study. Methods and Materials: 110 patients fulfilling our inclusion criteria were randomized (double-blinded) to receive naftopidil (50 mg) or tamsulosin (0.4 mg) once daily fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 20 publications
1
3
0
Order By: Relevance
“…In our study, naftopidil showed significant improvement in irritative components of IPSS mainly Frequency and Nocturia at 15 and 30 days of treatment which was supported by a recent comparative study conducted by Iqbal et al . [ 19 ] Tamsulosin showed better response in obstructive symptoms such as poor stream, intermittency and straining at 15 and 30 days of treatment which is similar to a comparative study reported by Ukimura et al . [ 18 ] and Nishino and Deguchi[ 16 ] in Japan.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…In our study, naftopidil showed significant improvement in irritative components of IPSS mainly Frequency and Nocturia at 15 and 30 days of treatment which was supported by a recent comparative study conducted by Iqbal et al . [ 19 ] Tamsulosin showed better response in obstructive symptoms such as poor stream, intermittency and straining at 15 and 30 days of treatment which is similar to a comparative study reported by Ukimura et al . [ 18 ] and Nishino and Deguchi[ 16 ] in Japan.…”
Section: Discussionsupporting
confidence: 84%
“…[ 18 ] and Iqbal et al . [ 19 ] Alpha-1D receptors have been found to be involved in the storage of urine in the bladder as was suggested by Chen et al ., the bladder capacity and urine volume per urination were significantly higher in alpha-1D knock-out mice than wild mice. [ 21 ] Thus, this report suggests that with relatively greater affinity to alpha-1D receptors, naftopidil can affect the storage function.…”
Section: Discussionmentioning
confidence: 89%
“…From the remaining 72 articles, 61 articles were excluded after the full text was assessed. Finally, 11 RCTs (Gotoh et al., 2005; Griwan et al., 2014; Hanyu et al., 2010; Ju et al., 2002; Kwon et al., 2018; Li et al., 2007; Masumori et al., 2009; Perumal et al., 2015; Singh et al., 2013; Ukimura et al., 2008; Yokoyama et al., 2011) were included to evaluate the efficacy and safety of naf versus tam in men with LUTS/BPH. A flow diagram is shown in Figure 1, which demonstrates the study selection process.…”
Section: Resultsmentioning
confidence: 99%
“…Ukimura et al (Ukimura et al., 2008) reported naf benefitted more in early improvement of urinary frequency and nocturia at 2 weeks than tam. Singh et al (Singh et al., 2013) also found that naf could improve the total IPSS, IPSS storage score, PVR and QoL earlier than tam. The reason for the early response may be based on the effect of naf on alpha1‐D receptors in the central neural system, spinal cord and bladder (Schwinn & Roehrborn, 2008).…”
Section: Discussionmentioning
confidence: 96%